An Evaluation of the Literacy Program in Islamic Religious Education Learning at SD-TQ Muadz Bin Jabal Kendari - Yus'an, Muhammad Taufiq; Herman, Herman; Akib, Akib (FITRAH: International Islamic Education Journal, 2025)
The literacy program is an initiative implemented in schools aimed at increasing students' interest in reading and writing. Specifically, at SD-TQ Muadz Bin Jabal Kendari, several activities are carried out to support the literacy program, including 15 minute reading sessions, reading in the library or reading corners, and the integration of literacy into subjects, particularly Islamic Religious Education (PAI). Therefore, this study aims to evaluate the School Literacy Movement (GLS) program at SD-TQ Muadz Bin Jabal Kendari and its application within the Islamic Religious Education learning process. This research uses a qualitative approach, with data collected through observation, interviews, tests, and documentation. The subjects of the study are the teachers (ustadz and ustadzah) and students of SD-TQ Muadz Bin Jabal Kendari. Data analysis techniques include data collection, data reduction, data display, and verification or conclusion drawing. The research findings reveal that the literacy program at SD-TQ Muadz Bin Jabal Kendari consists of several activities, such as reading in classroom reading corners or the library, and 15 minute reading sessions before lessons begin. The evaluation of the GLS program implementation includes: context evaluation literacy implementation is regulated by the principal's decree, establishing a literacy team; input evaluation the school is well prepared in terms of human resources (teachers and students), facilities (library and classrooms), and external support, particularly through collaboration with Nyalanesia to enhance school literacy; process evaluation literacy activities have been carried out fairly well, though further development and variation are needed to maintain student interest; product evaluation the GLS program has improved student learning outcomes, as shown by the 53% mastery rate in class 2C (which used literacy based learning) compared to only 33% in class 2D (which used conventional learning methods).